Perceptions, Attitudes, and Experiences Regarding Mental Health Care Among Young Black Men - Cortney VanHook (American Journal of Men's Health)
Mental health service research has insufficiently examined young Black men’s (YBM; ages 18–25) mental health care consumption patterns, obscuring their unmet mental health needs. Concurrently, the literature indicates YBM face unmet service needs that impede their ability to address numerous negative social determinants of health (e.g., high adverse childhood experiences, low socioeconomic status, etc.). Because preventing or treating mental health issues at or near onset can dramatically improve outcomes, this study utilizes thematic analysis to elucidate the factors most consequential to YBM’s experiences as mental health service consumers. Eight YBM ( M age  = 21.1 years) were purposively recruited to participate in semi-structured interviews to discuss attitudes regarding mental health care and cultural attitudes, gender-based attitudes, structural racism, and transition to adulthood. Of the eight participants, five had active health insurance, six had received mental health services before age 18 years, and three were currently receiving mental health services. Participants were attuned to their mental health needs and rejected stigmatizing attitudes about mental illness. Most participants reported hesitation about taking psychiatric medications. Participants had limited resources and encountered structural barriers to accessing mental health services. Most participants did not perceive racism as a source of mental distress. Culturally informed, consumer-oriented research is critical to tailoring and strengthening YBM’s mental health care. Future research should employ a population health approach to promote YBM’s mental health service uptake in adulthood.